Disasters, Poverty, and Coping Strategies: The Framework and Empirical Evidence from Micro/Household Data - Philippine Case - Danilo C. Israel; Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2014)
This study analyzed the interactions between natural disasters and household poverty and discussed the coping strategies used by households in response to natural disasters in the Philippines. It used data from the 2011 CBMS Household Profile Survey for Pasay City, Metro Manila and results of relevant past studies. The study found that a) there are existing analytical frameworks for the study of the interactions between natural disasters, household poverty, and household coping strategies; b) some empirical studies have been done in the Philippines analyzing the aforementioned interactions; c) relevant past studies generally point to the negative effect of natural disasters on household income and subsequently on household poverty; and d) past studies also showed that households practice several coping mechanisms to address the effects of natural disasters.Furthermore, based on own estimation done, the study found that the occurrence and frequency of typhoons and/or floods in Pasay City, Metro Manila have significant and negative effects on household per capita income. It concluded that for Pasay City and other similarly situated urban areas in the country, natural disasters have a negative impact on household income and consequently on household poverty. The study proposed future studies that can be conducted on the interactions between natural disasters and household poverty in the Philippines.
Keywords: 330; Philippines; natural disasters; floods; typhoons; household poverty; household coping strategies; Pasay City; Metro Manila